Simultaneous determination of amino acids in different teas using supercritical fluid chromatography coupled with single quadrupole mass spectrometry - Yang Huang; Tiejie Wang; Marianne Fillet; Jacques Crommen; Zhengjin Jiang (Elsevier, 2019)
Tea is a widely consumed beverage and has many important physiological properties and potential health benefits. In this study, a novel method based on supercritical fluid chromatography coupled with mass spectrometry (SFC-MS) was developed to simultaneously determine 11 amino acids in different types of tea (green teas, Oolong tea, black tea and Pu-erh tea). The separation conditions for the analysis of the selected amino acids including the column type, temperature and backpressure as well as the type of additive, were carefully optimized. The best separation of the 11 amino acids was obtained by adding water (5%, v/v) and trifluoroacetic acid (0.4%, v/v) to the organic modifier (methanol). Finally, the developed SFC-MS method was fully validated and successfully applied to the determination of these amino acids in six different tea samples. Good linearity (r ≥ 0.993), precision (RSDs ≤ 2.99%), accuracy (91.95%-107.09%) as well as good sample stability were observed. The limits of detection ranged from 1.42 to 14.69 ng/mL, while the limits of quantification were between 4.53 and 47.0 ng/mL. The results indicate that the contents of the 11 amino acids in the six different tea samples are greatly influenced by the degree of fermentation. The proposed SFC-MS method shows a great potential for further investigation of tea varieties. Keywords: Amino acids, Teas, Supercritical fluid chromatography with single quadrupole mass spectrometry (SFC-MS)